2015
DOI: 10.3945/ajcn.114.092601
|View full text |Cite
|
Sign up to set email alerts
|

Prospective association of fatty acids in the de novo lipogenesis pathway with risk of type 2 diabetes: the Cardiovascular Health Study

Abstract: In this large prospective cohort, circulating palmitic acid and stearic acid were associated with higher diabetes risk, and vaccenic acid was associated with lower diabetes risk. These results indicate a need for additional investigation of biological mechanisms linking specific fatty acids in the DNL pathway to the pathogenesis of diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
104
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(119 citation statements)
references
References 59 publications
12
104
1
2
Order By: Relevance
“…Overall, the estimated D6D and SCD1 activities were strongly associated and the estimated D5D activity was inversely associated with the development of type 2 diabetes, as previously reported [14,27]. We also showed that the most abundant SFAs were associated with an elevated risk of diabetes, in agreement with two recent studies showing associations with type 2 diabetes [17,28]. Total SFAs were associated with impaired insulin sensitivity and insulin secretion in our study, offering a mechanistic explanation for how SFAs may impair glucose tolerance and lead to type 2 diabetes.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Overall, the estimated D6D and SCD1 activities were strongly associated and the estimated D5D activity was inversely associated with the development of type 2 diabetes, as previously reported [14,27]. We also showed that the most abundant SFAs were associated with an elevated risk of diabetes, in agreement with two recent studies showing associations with type 2 diabetes [17,28]. Total SFAs were associated with impaired insulin sensitivity and insulin secretion in our study, offering a mechanistic explanation for how SFAs may impair glucose tolerance and lead to type 2 diabetes.…”
Section: Discussionsupporting
confidence: 81%
“…First, the diagnosis of type 2 diabetes has often been selfreported or based only on fasting glucose measurement [7,16], or diagnostic criteria have not been reported [17]. Second, none of previously published studies evaluated incident diabetes based on an OGTT or on HbA 1c levels.…”
Section: Introductionmentioning
confidence: 99%
“…This relationship between C16:0 and glucose intolerance has been previously reported in other studies 22,23 and enforces the validity of this study.…”
Section: -Hydroxyacyl-coa Lyase 1 (Hacl1) Study To Further Investigsupporting
confidence: 60%
“…The replacement of SFAs with MUFAs and PUFAs or replacement of trans-fat with MUFAs was inversely associated with CVD [11].…”
mentioning
confidence: 95%
“…Experimentally determined SFA 14:0 and 16:0 status correlates positively with increased total cholesterol (TC/HDL) ratio while FA intake does not [1,6]. The status and intake of C-18 SFA (stearic) is neutral on lipids, lauric C-12 increases LDL, HDL (18:1 n7) is inversely associated with T2 DM [11].…”
mentioning
confidence: 99%